GroupBar: The TaskBar Evolved - Smith, Greg; Baudisch, Patrick; Robertson, George; Czerwinski, Mary; Meyers, Brian; Robbins, Daniel ((2003) OZCHI 2003 Conference for the Computer-Human Interaction Special Interest Group of the Human Factors Society of Australia, 2003)
Our studies have shown that as displays become larger, users leave more windows open for easy multitasking. A larger number of windows, however, may increase the time that users spend arranging and switching between tasks. We introduce GroupBar, a task management system for dealing with the profusion of windows on the PC desktop. Designed to offer the same basic form and function as the existing Microsoft Windows™ TaskBar, GroupBar additionally allows users to group windows into higher-level tasks and enables task switching with a single mouse click. In order to gain experience with GroupBar usage and to develop reasonable task definitions we conducted a longitudinal field study. Based on the results of that field study, we conducted a comparative user study wherein we found that participants were able to multitask faster when using GroupBar than when using the existing Windows TaskBar.